Недостаточность надпочечников: лекция / Г. П. Шульцев - Шульцев Георгий Павлович (ЦОЛИУВ, 1989)
Экземпляры: КХ (20111011) / Инвентарный номер: 0285535 / Цена: 0.05 / Сис.шифр: 54.15 / Авт.знак: Ш 95 / ГРНТИ: 76 / ББК: 54.151.7